Determinan Keputusan Pembelian Pada E-Commerce Shopee: Perspektif Live Streaming, Diskon dan Gratis Ongkos Kirim - Tia Chisca Anggraeni (Journal of Trends Economics and Accounting Research, 2024)
The aim of this research is to determine the influence of Live streaming, Price Discounts and Free Shipping on Purchasing Decisions on Shopee E-commerce partially and simultaneously. The analysis method in this research uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, T Test (Partial), F Test (Simultaneous), and Coefficient of Determination Test (R2). The data used in this research is primary data obtained using a questionnaire instrument with a sample size of 100 respondents. The method for taking this sample is non-probability sampling with a purposive sampling technique. Data was processed using SPSS v.23 tools. Based on the results of the T test research, it shows that the Live streaming variable partially has no and significant influence on the purchasing decision variable. Meanwhile, the Price Discount and Free Shipping variables partially have a positive and significant effect on purchasing decisions on Shopee e-commerce. Then the results of the F test show that the variables Live streaming, Price Discounts and Free Shipping simultaneously have a significant influence on purchasing decisions on Shopee e-commerce. The results of the coefficient of determination (R2) show that the influence of Live streaming, Price Discounts and Free Shipping on purchasing decisions is 59.7%, while the remaining 40.3% is the contribution of other variables not included in this research, for example service quality, promotions, and so on.